Prognosis: a fundamental ethical commitment for the informed consent - Nelson Cortés-C. (Revista Facultad de Odontología Universidad de Antioquia, 2006)
The process that makes the Informed Consent possible is based on several dialogues between the dentist and the patient. The Prognosis is a basic component of the dental history, linking the diagnosis and the treatment plan and allowing the professional to synthesize in the document of acquiescence the therapeutic proposal, including benefits and risk. The course of events the dentist has to follow in this process could be summarized in the following way: Identification of the problem —as the initial step in the clinical exam—; reaching a diagnosis —definition of the state of health—; prescription of the treatment plan —offering the several treatment options with their defined objectives—; formulation of the prognosis —the best way to anticipate the positive and negative results—; formalize the acquiescence —with the patient’s signature as the legal base for his/her acceptance as a permission to be treated—; limit the clinic action —for the procedures defined and in the areas of her/his body, previously determined—; revision of the treatment plan —when, during the course of care, if necessary, for many reasons, reformulate the initial proposal.